Permodelan Sistem Informasi Penjualan Barang Berbasis Website Menggunakan Metode Agile - Sandi Badiwibowo Atim (PT. Tech Cart Press, 2024)
Goods sales information system is an important infrastructure for companies to manage and track all sales transactions of their goods efficiently. One common problem is the system's inability to handle high transaction volumes quickly and efficiently, especially during busy sales periods. This study aims to create a website-based goods sales information system by applying agile methods in design so that it can overcome existing problems and accelerate when there is a change process in design. In modeling a website-based goods sales information system using the Agile method, the result is the development of a system that is more adaptive and responsive to changing business and user needs. The Agile method allows for gradual system development, focusing on delivering features that have high added value in each iteration. The results of blackbox testing show that the website-based goods sales system reflects a high success rate, reaching 100%. This indicates that the system has successfully passed a series of functionality, security, compatibility, and performance tests without finding significant defects or errors.